ELONGATED STYLOID PROCESS: AN ANATOMICAL FINDING AND A LITERATURE REVIEW OF ITS CLINICAL IMPLICATIONS IN EAGLE’S SYNDROME - Aragão, José Aderval; Jacó Carvalho, Adler Oliveira Silva; Routman da Cunha, Henrique Montalvão; Rezende Santos, André Elias; Sá Costa, Giovanna de Oliveira; Pinto de Menezes, Lorena; Santos Junior, Gilvan Paixão; Alexandre Lima, Wallance Geovane; Lima Passos, Ryan Kelvin; Souza Santos, Enzo; Andrade Cunha, Davi; Sant’Anna Aragão, Iapunira Catarina; et al. (Brazilian Journal of Implantology and Health Sciences, 2025)
Introduction: The styloid process (SP) is a slender bony projection located on the inferior surface of the petrous part of the temporal bone. Its length varies from 25-30 mm, being considered elongated when it exceeds 30 mm. The causes of styloid process elongation are not well defined, and several theories have been proposed, such as congenital elongation due to the persistence of a cartilaginous embryonic sheet, calcification of the stylohyoid ligament resulting in the appearance of an elongated styloid process, and bone tissue formation at the stylohyoid ligament attachment. Objective: To report the occurrence of an elongated styloid process. Materials and Methods: It was an anatomical, observational finding in a dry skull belonging to the Anatomy Laboratory of the Federal University of Sergipe (UFS). The finding was documented through photographs taken with a digital camera (SONY DSLR-A100K) and morphometry of the styloid process was performed with a Vonder digital caliper. Results: An elongated styloid process was found at the inferior base of a dry human skull, with a solder line of its anteroposterior projection suggesting it is the stylohyal and ceratohyal division of the hyoid apparatus. The styloid process had a length of 55.84 mm and proximal, middle, and distal thickness of 6.59 mm, 4.44 mm, and 2.12 mm, respectively. Conclusions: The presence of an elongated styloid process greater than 40 mm in length is key to the diagnosis of Eagle syndrome, characterized by cervicofacial pain and dysphagia. Accurate diagnosis is vital for the differentiation and management of symptoms, despite the unknown etiology. Further research is crucial for anatomical and clinical understanding.